Glycogen Synthesis is Induced in Hypoxia by the Hypoxia-Inducible Factor and Promotes Cancer Cell Survival - Pelletier, Joffrey; Bellot, Gregory; Gounon, Pierre; Lacas-Gervais, Sandra; Pouyssegur, Jacques; Mazure, Nathalie M. (Frontiers in Oncology, 2012)
The hypoxia-inducible factor 1 (HIF-1), in addition to genetic and epigenetic changes, is largely responsible for alterations in cell metabolism in hypoxic tumor cells. This transcription factor not only favors cell proliferation through the metabolic shift from oxidative phosphorylation to glycolysis and lactic acid production but also stimulates nutrient supply by mediating adaptive survival mechanisms. In this study we showed that glycogen synthesis is enhanced in non-cancer and cancer cells when exposed to hypoxia, resulting in a large increase in glycogen stores. Furthermore, we demonstrated that the mRNA and protein levels of the first enzyme of glycogenesis, phosphoglucomutase1 (PGM1), were increased in hypoxia. We showed that induction of glycogen storage as well as PGM1 expression were dependent on HIF-1 and HIF-2. We established that hypoxia-induced glycogen stores are rapidly mobilized in cells that are starved of glucose. Glycogenolysis allows these “hypoxia-preconditioned” cells to confront and survive glucose deprivation. In contrast normoxic control cells exhibit a high rate of cell death following glucose removal. These findings point to the important role of hypoxia and HIF in inducing mechanisms of rapid adaptation and survival in response to a decrease in oxygen tension. We propose that a decrease in pO2 acts as an “alarm” that prepares the cells to face subsequent nutrient depletion and to survive.